Quality of life and psychological compatibility in light of the precautionary measures of the Corona pandemic from the point of view of a sample of individuals in the city of Makkah Al-Mukarramah - Alghamdi, Badryah Faisal; Neyaz, Sawsan Mohammed; Alomari, Wafa Ahmed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the level of both quality of life and psychological compatibility among a sample of individuals in the city of Makkah Al-Mukarramah in light of the precautionary measures for the Corona pandemic, and to examine the extent to which there are statistically significant differences between the averages of the sample answers regarding quality of life and the level of psychological compatibility due to the gender variable (males - females). And the extent of a statistically significant relationship between the quality of life and the level of psychological compatibility of individuals in the city of Makkah Al-Mukarramah in light of the precautionary measures for the Corona pandemic. The researchers used the descriptive approach, and the tool consisted of two scales; The first: the quality of life scale prepared by Bushra Ismail (2008), and the scale consists of (26) phrases, divided into (4) dimensions, and the second is the psychological compatibility scale prepared by Zainab Shukair (2003), and it consists of (80) phrases in (4) Dimensions, and they were applied to a sample of (50) individuals who were randomly selected from the residents of the city of Makkah Al-Mukarramah, Kingdom of Saudi Arabia (ages between 18-60 years). The analysis was carried out using the statistical program (SPSS), and the results showed the following:The dimension of mental health in the axis of quality of life got the highest average (2.29), then physical health, and the environment, both of them with an average of (2.25), and fourthly, social relations with an average of (2.15), and the dimension of health compatibility in the axis of psychological compatibility got the highest average (3.00) at a level of (high). then social adjustment with an average of (2.44), and thirdly, personal-emotional with an average of (2.43) and fourthly, family with an average of (2.29(.There are differences in the averages according to gender between males and females in the impact of the level of quality of life related to each of the axis (physical health - social relations - environment) that are attributed in favor of females.
Keywords: quality of life; psychological compatibility; the holy city of Makkah; Corona